Weird : the Al Yankovic story [videorecording (DVD)] - Appel, Eric, 1980-; Yankovic, Al, 1959-; Yankovic, Al, 1959-; Radcliffe, Daniel, 1989-; Wood, Evan Rachel, 1987-; Wilson, Rainn, 1966-; Huss, Toby, 1966-; Castro, Arturo, 1985-; Nicholson, Julianne, 1971- (Shout! Factory, 2023)
Daniel Radcliffe is "Weird" Al Yankovic in the unexaggerated true story about the greatest musician of our time. From a conventional upbringing where playing the accordion was a sin, Al rebelled and made his dream of changing the words to world-renowned songs come true. An instant success and sex symbol, Al lives an excessive lifestyle and pursues an infamous romance that nearly destroys him.